Pengaruh Penanaman Modal Asing, Penanaman Modal Dalam Negeri, Dana Perimbangan, dan Aglomerasi terhadap Ketimpangan Pembangunan antar Wilayah di Provinsi Banten Tahun 2011-2020 - Galuh Gita Lestari; Mulyo Hendarto Robertus (Universitas Diponegoro, 2023)
Regional disparity is a common phenomenon in the process of regional economic development in developing countries. In order to reduce regional disparity, it is necessary to study the factors that influence regional disparity. This research aims to analyze the effect of Foreign Direct Investment (PMA), Domestic Direct Investment (PMDN), Balancing Funds, and Agglomeration on Regional Development Disparity in Banten Province in the 2011-2020 period. This study uses panel data regression analysis with the Random Effect Model (REM) approach. The regression results with the Random Effect Model (REM) approach with the Generalized Least Square (GLS) method show that in 2011-2020, partially the variables of foreign direct investment, domestic direct investment, and agglomeration have no a significant effect, and only the balancing fund variable has a significant effect on regional development disparity in a negative direction.